Urban Poverty: A Sociological Study of Shankhamul Squatter - Acharya, Bala Ram (Dhaulagiri Journal of Sociology and Anthropology, 2011)
The paper aims to identify the nature of poverty of squatter of Kathmandu valley in the context of exploring urban poverty. It has conceptualized poverty, urbanization, slum, and squatter. It has explored the social, economic and political background of squatter people. This paper also explores the nature of access of squatter people to basic requirements. It has discussed that squatter is a social formation formed by rural-urban migration of poor people to search options of livelihood. Keywords: Poor; slum area; migration; urbanization; livelihood DOI: 10.3126/dsaj.v4i0.4519 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.179-192